Nilai Kesempurnaan Kristen dalam Kitab Ibrani - Seri Damarwanti (SANCTUM DOMINE: JURNAL TEOLOGI, 2016)
Christian perfection is not just an expression that contains expectations for Christians, but rather a standard of living that is commanded and required for every Christian. The book of Hebrews teaches that the values ​​of Christian Perfection are closely related to holiness, with Perfection being the nature of God and the result of his work. Christian perfection is perfection that originates from Holiness of life, of love and of motivation , from and understanding and recognition that Christ’s saving work completely resolves the problem of sin, and is valid for ever. Perfection is seen and birthedin the figure of Jesus Christ our High Priestas well as the perfect sin offering, who completed his work of attonement in the more perfect heavenly Tablernacl, not made by human hands.Christian perfection is inseparable from the meaning of Holiness, demanded of all Christians.